Effectiveness of Online and Offline Educational Media in Increasing Pregnant Women's Knowledge about the Warning Signs of Preeclampsia in Rural Aceh Besar Regency - Sari, Yuni; Nurbaiti, Nurbaiti (PT. Riset Press International, 2024)
This study explores the effectiveness of online and offline educational media in enhancing pregnant women's knowledge about the warning signs of preeclampsia in rural Aceh Besar District. Preeclampsia is a serious pregnancy complication that can lead to severe health risks for both mothers and infants, making education on its warning signs essential. A quasi-experimental design was utilized, involving three groups of pregnant women: one group received education through an animated video, the second group was provided with an online booklet, and the third group received an offline booklet. The study included pre-test and post-test assessments to evaluate knowledge improvement, followed by statistical analysis using the Wilcoxon signed-rank test and the Kruskal-Wallis test to determine the effectiveness of each intervention. The results revealed significant increases in average post-test scores across all groups, with a p-value of 0.000 indicating strong statistical significance. The video group demonstrated the highest improvement, with pre-test scores averaging 72.10 and post-test scores rising to 86.30, resulting in an increase of 14.20. The online booklet group showed a substantial increase as well, with pre-test scores of 68.70 rising to 81.00, reflecting an increase of 11.90. Similarly, the offline booklet group experienced an increase from 72.60 to 81.20, marking an increase of 8.60. These findings underscore the effectiveness of all intervention methods in improving knowledge about preeclampsia among pregnant women. Notably, the animated video emerged as the most effective educational tool, demonstrating its potential to engage and inform effectively.